Parenting Module for Parents of Children with Mental Retardation to Improve Understanding in Parenting - Aulia Nailul Muna; Sunardi Sunardi; Herry Widyastono (Jurnal Pendidikan Indonesia, 2021)
This study aims to produce media in the form of parenting modules for parents of children with mental retardation that suitable to be used by the parents. Some things that are important in this study include increasing the knowledge and understanding of parents of children with mental retardation so that they can care for the children according to their abilities. In addition, they can develop optimally, and solve problems faced by parents of children with mental retardation. It provides solutions toward the parents’ problems so that children with mental retardation can grow and develop properly. This study uses Research and Development (R&D) based on Borg and Gall. The conducted stages include research and data collection, planning, product draft development, product testing, and revision of product trial results. This product was tested on 21 parents of children with mental retardation. The feasibility of the product is based on the evaluation results of material experts, media experts, and parents of students as test subjects. Data collection techniques used observation, interviews, questionnaires, and documentation. Data analysis at the problem identification stage used descriptive analysis. While the data analysis technique used on product quality is quantitative descriptive data analysis. The results showed that the parenting module media for parents of children with mental retardation was developed through a series of trials, and expert validation was declared feasible.